The effect of methionine and threonine supplementations on immune responses of broiler chickens challenged with infectious bursal disease - Maroufyan, Elham; Kasim, Azhar; Hashemi, Seyed Reza; Loh, Teck Chwen; Bejo, Mohd Hair; Davoodi, Homa (Science Publications, 2010)
Problem statement: The aim of this study was conducted to determine the effects of supplementing methionine and threonine higher than the National Research Council (NRC) recommendation in the diets on immune responses of broiler chickens challenged with Infectious Bursal Disease (IBD). Approach: A total of 450 day-old male broiler chicks were assigned to one of the nine dietary treatments. Three levels of methionine (NRC (M1), 2 times NRC (M2) and 3 times NRC (M3)) and 3 levels of threonine (NRC (T1), 2 times NRC (T2) and 3 times NRC (T3)) were fed. On day 28, all birds were challenged with a commercial live-IBDV vaccine. Results: Antibody titer against IBD and ND were influenced by interaction of threonine and methionine. On 7 days after IBD challenge, ND antibody titer of the broilers receiving the highest level of methionine and threonine was significantly higher than that of other treatment groups. Lesion score of the bursa of the broilers receiving control diet was significantly the highest compared with the other treatments. Conclusion/Recommendations: The results obtained on the present study indicated that threonine and methionine requirements of broiler based on recommendation of NRC are not sufficient to meet the requirement of the new commercial poultry and commercial broiler companies under non-hygienic condition.